Improved Moscovian part of the Gondwana APWP for paleocontinental reconstructions, obtained from a first paleomagnetic pole, age-constrained by a fold test, from In Ezzane area in the Murzuq basin (Algeria, stable Africa) - (:unkn) unknown (My University, 2014)
To improve paleocontinental reconstructions, paleomagnetic reference curves (Apparent Polar Wander Path: APWP) feature for large continents have to be continuously refined by adding up new high-quality data. For stable Africa, the Moscovian period was favorable for such aim, with well-dated and widespread geological formations. A new study has been conducted in the Upper “Dembaba” geological formation of Lower Moscovian age outcropping in the western part of the “Murzuq” basin (Saharan platform). Well-defined ChRMs, combined with remagnetization circles data, both constrained in age by a positive fold test, yield a new significant paleomagnetic pole (λ = 25.2°S, ϕ = 59.9°E, K = 55, A95 = 5.4°). When joined with previous African data of the same age, it gives an improved reference pole for Africa (λ = 28.9°S, ϕ = 54.5°E, K = 106, A95 = 3.6°). The Mean Moscovian paleomagnetic pole determined from an updated Gondwana Paleozoic APWP (λ = 29.4°S, ϕ = 51.5°E, K = 11, A95 = 1.8°), associated with the corresponding Laurussia pole (Domeier et al., 2012), yields a more constrained paleocontinental reconstruction for 310 Ma.
Keywords: African Research